Homologies of spinal ascending nociceptive pathways between rats and macaques: can we transpose to human? A review and analysis of the literature. - Dabala, Eric; Guédon, Alexis; Ficheux, Guillaume; Béal, Louis; Moxham, Bernard; Plaisant, Odile (Surgical & Radiologic Anatomy, 2023)
Purpose: Due to the difficulty of using neural tracers in humans, knowledge of the nociceptive system's anatomy is mainly derived from studies in animals and mainly in rats. The aim of this study was to investigate the morphological differences of the ascending spinal nociceptive pathways between the rat and the macaque monkey; in order to evaluate the variability of this anatomy during phylogenesis, and thus to know if the anatomical description of these pathways can be transposed from the rat to the human. Methods: A review and analysis of the literature were performed. The criteria used for comparison were: origins, pathways, their terminations in target structures, and projections from target structures of ascending spinal nociceptive pathways. The monkey was used as an intermediate species for comparison because of the lack of data in humans. The hypothesis of transposition of anatomy between rat and human was considered rejected if differences were found between rat and monkey. Results: An anatomical difference in termination was found for the spino-annular or spino-periaqueductal grey (spino-PAG) pathway and transposition of its anatomy from rat to human was rejected. No difference was found in other pathways and the transposition of their anatomy from rat to human was therefore, not rejected. Conclusion: This work highlights the conservation of most of the ascending spinal nociceptive pathways' anatomy between rat and monkey. Thus, the possibility for a transposition of their anatomy between rat and human is not rejected.